2018
DOI: 10.1080/1461670x.2018.1492882
|View full text |Cite
|
Sign up to set email alerts
|

Transparency to the Rescue?

Abstract: Transparency has emerged as an ethical principle in contemporary journalism and is contended to improve accountability and credibility by journalists and scholars alike. However, to date, few attempts have been made to record the public's views on transparency. This study enriches current knowledge by using data from an experiment, survey and focus groups in Sweden collected between 2013 and 2015. Overall, the results suggest that the respondents are not particularly moved by transparency in any form; it does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…10 Research has shown that journalist’s inclusion of links in news articles to source documents, including scientific studies, increases readers’ perceived transparency of the story and positively influences their perceptions of media credibility. 38 In this study, participants confirmed this research by noting the link presence as a cue for credibility. However, while this is encouraging, participants’ behaviour, which included limited clicking of links to the included scientific papers, suggests a potentially missed opportunity for further learning and signals a need for future research to understand the hesitation to click and directly engage with primary research sources.…”
Section: Discussionsupporting
confidence: 72%
“…10 Research has shown that journalist’s inclusion of links in news articles to source documents, including scientific studies, increases readers’ perceived transparency of the story and positively influences their perceptions of media credibility. 38 In this study, participants confirmed this research by noting the link presence as a cue for credibility. However, while this is encouraging, participants’ behaviour, which included limited clicking of links to the included scientific papers, suggests a potentially missed opportunity for further learning and signals a need for future research to understand the hesitation to click and directly engage with primary research sources.…”
Section: Discussionsupporting
confidence: 72%
“…Pozil and Hacker, 2017; Schnackenberg and Tomlinson, 2016; Shapiro, 1987; Wheeless and Grotz, 1977), our findings differ from the study most closely related to the present endeavor: Karlsson et al (2014) conclude that transparency elements do not affect credibility ratings. It is not possible to know why our results differ without further research, but differences in the context (US vs Sweden; see Karlsson and Clerwall, 2018), approach (testing multiple transparency elements at once vs one at a time), and statistical power (approximately 65 study participants per condition vs the approximately 200 participants per condition in this study) seem reasonable candidates. The US context in particular may be unique, given the low levels of media trust.…”
Section: Discussionmentioning
confidence: 84%
“…Skeptics of transparency’s ability to restore news credibility also have experimental support. Karlsson and colleagues (2014, 2018) envisioned transparency elements as containing information about corrections to a story, information about and a link to earlier versions of the story, an explanation of how and why a story was written, the disclosure of a journalist’s opinion about the story being reported, timestamps detailing when the article was published, and internal and external hyperlinks. Their study tested each of 20 transparency elements separately, compared to a control condition with no transparency elements.…”
Section: Credibility and Transparencymentioning
confidence: 99%
See 2 more Smart Citations